Performance Evaluation of SHOX2 and RASSF1A Methylation for the Aid in Diagnosis of Lung Cancer Based on the Analysis of FFPE Specimen - Shi, Juanhong; Chen, Xue; Zhang, Long; Fang, Xia; Liu, Yuting; Zhu, Xuyou; Zhang, Haoyang; Fan, Lichao; Gu, Jun; Zhang, Suxia; She, Bin; Han, Hongxiu; et al. (Frontiers in Oncology, 2020)
Emerging molecular diagnostic methods are more sensitive and objective, which can overcome the intrinsic failings of morphological diagnosis. Here, we developed and characterized a RT-PCR-based in vitro diagnostic test kit (LungMe®) to simultaneously quantify the DNA methylation of SHOX2 and RASSF1A in FFPE tissue specimens. The clinical manifestations were evaluated in 251 FFPE samples with specificity and sensitivity of 90.4% and 89.8%, respectively. Furthermore, the quantitative analysis shows that the degree of SHOX2 methylation was correlated with the stages of lung cancer, but not in the case of RASSF1A. Our observation indicated that the DNA methylation of these two genes may play different roles in cancer development. Comparison of the methylation levels of SHOX2 and RASSF1A between cancer and cancer-adjacent specimens (n=30), they were found to have “epigenetic field defect”. As additional clinical validation, the hypermethylation of SHOX2 and RASSF1A were detected not only in 16/17(94%) of the surgical operative specimens, but also in 11/17 (65%) of those pairs of histopathological negative puncture biopsies. Utilizing SHOX2 and RASSF1A methylation detection can increase the sensitivity and NPV. This provides us with a more accurate method of differential diagnosis and is likely to be rapidly applied in clinical examinations.